Cyclodextrin-based rotaxanes - Stanier, C; C. A. Stanier (2002)
﻿ A series of novel [2]rotaxanes of general formula 1 has been synthesised, exploiting the hydrophobic effect to cause binding inside α- or β-cyclodextrin cavities, and making use of Suzuki coupling to stopper the rotaxane. The size complementarity of the dumbbell and cyclodextrin units was investigated. The rotaxanes were characterised by use of 2D NMR techniques and, in one case, by X-ray crystallography. The reactivity of one such rotaxane (α-cyclodextrin, stilbene core and carboxylic acid stoppered) was investigated by comparison with the corresponding dumbbell. The presence of the cyclodextrin was shown to have a protective influence towards some reactants. The absorption and emission properties of these rotaxanes were compared. We have demonstrated an increase in the fluorescence quantum yield by up to a factor of three. The photo-induced isomerisation of all the stilbene-based rotaxanes and dumbbells synthesised was surveyed; in one case it was found that encapsulation had completely prevented this isomerisation. A quantitative investigation of the proportions and extinction coefficients of the trans and cis isomers of one rotaxane in the photostationary state was undertaken, and the quantum yields of switching deduced. The rate of photodegradation and the ultimate products of this were investigated. The major photoproduct in both cases arose through photo-induced hydration of the stilbene double bond. The final chapter is concerned with attempts to synthesise rotaxanes by reaction of a 1,3,5-triazine with an azo dye (2). Related rotaxanes have been successfully prepared in the past1-3 , however in this instance the attempts did not result in significant amounts of rotaxane formation. This was rationalised by the shorter length of the dye. The thesis as a whole illustrates the stabilisation of chromophores that is possible through the formation of rotaxanes.